Aqueous extract of Phragmitis rhizoma ameliorates myelotoxicity of docetaxel in vitro and in vivo - Jinhee Kim; You Jin Lee; Young Ah Kim; Eun-Sang Cho; Eunna Huh; Ok-Sun Bang; No Soo Kim (BMC, 2017)
Abstract Background A variety of anticancer chemotherapeutics induce adverse side effects including myelotoxicity. Dried roots of Phragmites communis Trinius, Phragmitis rhizoma, have been clinically used in traditional folk medicine to relieve various symptoms like fever. In this study, we evaluated the protective effect of the aqueous extract of Phragmitis rhizoma (EPR) against docetaxel-induced myelotoxicity in vitro and in vivo. Methods The in vitro myelo-protective effect of EPR was evaluated using the colony forming unit (CFU) assay with hematopoietic progenitor cells. The in vivo efficacy of EPR was evaluated in myelosuppressed C57BL/6 male mice which were induced by repeated intraperitoneal injections of 30 mg/kg docetaxel for 3 times. EPR was orally administered for 4 days to docetaxel-induced myelosuppressed C57BL/6 male mice which were induced by intraperitoneal injection of 30 mg/kg docetaxel for 3 times: Group 1 (vehicle control, n = 10), Group 2 (docetaxel plus vehicle, n = 10), Group 3 (docetaxel plus EPR 30 mg/kg, n = 10), Group 4 (docetaxel plus EPR 100 mg/kg, n = 10) and Group 5 (docetaxel plus EPR 300 mg/kg, n = 10). Whole blood counts were measured automatically, and immune organs were histologically examined. Expression of immunomodulatory cytokines was measured by quantitative real-time polymerase chain reaction or enzyme-linked immunosorbent assay. The toxicity of EPR itself was evaluated in normal human cell lines including IMR-90, foreskin fibroblast and human umbilical vein endothelial cells. The hepatotoxicity of EPR was predicted by multi-parametric assays involving cell viability, caspase 3/7 activity, GSH contents and LDH leakage using the HepaRG hepatic cell line. Results Co-treatment of EPR or its major component, p-hydroxycinnamic acid, increased the numbers of hematopoietic CFU counts in the docetaxel-induced in vitro myelotoxicity assay system. The in vitro protective effect of EPR against docetaxel toxicity was replicated in a myelosuppressed animal model: white blood cells, neutrophils, lymphocytes and red blood cells rebounded; bone marrow niche and structural integrity of the thymus were preserved; and the expression of immune-stimulating cytokines including IL3, IL6, SCF and GM-CSF was enhanced. Furthermore, EPR and p-hydroxycinnamic acid promoted the proliferation of primary splenocytes and thymocytes. In the toxicity assays, no remarkable signs related with toxicity were observed in all tested normal human cells and HepaRG. Conclusions EPR has the potential to ameliorate docetaxel-mediated myelotoxicity in both in vitro and in vivo models. However, the identification of the responsible active components and the precise underlying myelo-protective mechanism of EPR need to be elucidated before novel drug development using EPR can precede.